Valuing the bowling alley: Contestations over the preservation of spaces of everyday urban multiculture in London. Issue 1 (January 2019) - Jackson, Emma
This article builds on 'the convivial, everyday turn' by approaching the workings of complex urban spaces of multiculture as entangled with processes of urban change that are infused with judgements and contestations about what is of value. The article explores the competing value claims made for a leisure space, a London bowling alley, used by a diverse group of people (in terms of dis/ability, ethnicity, gender, class and age) that has been threatened with demolition. It examines how arguments about diversity and inclusivity are deployed in these debates and how official discourses are resisted through the mobilisation of other articulations of social value. The article argues that the combination of the hollowing out of the concept of diversity and the political and economic context results in a paradox whereby multiculturalism is celebrated as an atmosphere and generator of capital while existing physical spaces of everyday urban multiculture are at best unprotected and at worst not recognised, devalued and demolished.